Immune checkpoint inhibitors promising role in cancer therapy: clinical evidence and immune-related adverse events - Meybodi, Seyed Mohammadmahdi; Far, Bahareh Farasati; Pourmolaei, Ali; Baradarbarjastehbaf, Farid; Safaei, Maryam; Mohammadkhani, Niloufar; Samadani, Ali Akbar (Humana Press Inc, 2023)
The advent of immune checkpoint inhibitors (ICIs) has led to noteworthy progressions in the management of diverse cancer types, as evidenced by the pioneering ipilimumab medication authorized by US FDA in 2011. Importantly, ICIs agents have demonstrated encouraging potential in bringing about transformation across diverse forms of cancer by selectively targeting the immune checkpoint pathways that are exploited by cancerous cells for dodging the immune system, culminating in progressive and favorable health outcomes for patients. The primary mechanism of action (MOA) of ICIs involves blocking inhibitory immune checkpoints. There are three approved categories including Programmed Death (PD-1) inhibitors (cemiplimab, nivolumab, and pembrolizumab), Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) (Ipilimumab), and Programmed Death-Ligand 1 (PDL-1) (Avelumab). Although ICIs promisingly increase therapeutic response and cancer survival rates, using ICIs has demonstrated some limitations including autoimmune reactions and toxicities, requiring close monitoring. The present review endeavors to explicate the underlying principles of the MOA and pharmacokinetics of the approved ICIs in the realm of cancer induction, including an appraisal of their level of practice-based evidence. [GRAPHICS]
Keywords: Cancer therapy; ICIs; Immunotherapy; Tumor biomarker